The effect of inquiry-based learning style in learning the skill of front rolling in artistic gymnastics for second-stage students in the Faculty of Physical Education and Sports Sciences according to their double coding - kaab , Doaa; Gatia, Aseel (Journal of Physical Education, 2024)
The research aims to identify the effect of employing the method of learning based on inquiries in educational exercises to learn the anterior skill in opening the technical gymnasium, and to know the effect of the method of learning based on inquiries in learning the anterior skill of opening in the artistic gymnasium for students of the second stage in the Faculty of Physical Education and Sports Sciences on According to their double coding, the experimental curriculum was adopted by the experimental design with the two experimental groups and the operational control (2 x 3) on a sample of (79) students who were traditionally chosen by (88.764%) of their community of originally (89) students represented by the students of the second stage in the College of Physical Education and Science Sports at the University of (Kirkuk) is continuing with the official urban development in the morning study for the academic year (2023/2024) for the first semester, Then they divided into implicit groups (6) within these two groups according to their double coding, and after identifying the skill test and preparing educational exercises for this experimenting method by applying tribal tests on Tuesday corresponding to the date (11/14/2023), and ended on Wednesday, the date of date (11/30/2023), the application (4) included educational units for this skill over two consecutive weeks, and then the grades were collected and statistically addressed with the SPSS system, and the conclusions were that it is possible to apply the vocabulary of the learning method based on inquiries in the lessons of physical education The volleyball operation for the second stage in the College of Physical Education and Sports Science, And that the application of the method of learning based on inquiries helps in learning the skill of the anterior argument in opening with the technical gymnastics among students of the second stage in the College of Physical Education and Sports Sciences more suitable for people with dual coding, followed by those with graphic coding, followed by verbal coding, and excels to learn it with students who study without them, It is necessary to focus on the practical applications of the methods of stimulating students learning to inquire more than the explanations and guidance in the educational units of the technical gymnastics to increase students ’empowerment to practice and apply based on the discovery of knowledge with performance.